EVALUATION OF DIGITAL DETECTOR ARRAYS SYSTEMS FOR INDUSTRIAL RADIOGRAPHY (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Digital Detector Arrays (DDA) or Flat Panel Detector (FPD) is a highly efficient technique that is used in nondestructive testing of internal features of an object. The evaluation of DDA systems for industrial radiography is important to ensure the image quality and to enables long-term stability of this system. This evaluation is specified by ASTM E2737–10, which describes the fundamental parameters of DDA systems to be measured. The tests require the usage of either the five-groove wedge or the duplex plate phantom with separate Image Quality Indicators (IQIs). The purpose of this work was evaluate the radiographic performance achieved using both techniques in two DDA systems manufactured by GEIT: DXR250P and DXR250V, which have thallium-doped cesium iodide (CsI:Tl) and terbium-doped gadolinium oxysulfide (Gd2O2S:Tb - GOS) scintillators, respectively. For this purpose, it was used an X-ray equipment as radiation source. The image quality parameters analyzed were Image Lag (IL), Offset Level (OL), Bad Pixel distribution, Burn In (BI), Spatial Resolution (SR), Material Thickness Range (MTR), Contrast Sensitivity (CS), Signal Level (SL) and Signal-to-Noise Ratio (SNR). As result of this study, has been observed that the use of the five-groove wedge phantom made the measurements to become easier to execute. Regarding the DDA system, the DXR250P presented more IL and BI, but produced images with better CS and SNR and needed a dose almost twice smaller than the DXR250V to achieve a similar SL.